Anti-ceramide antibodies in leprosy: marker for nerve damage? - Singh, Kalpana; Singh, Bhawna; Ray, Prakash (The Journal of Infection in Developing Countries, 2010)
Background: Leprosy is a chronic infectious disease primarily affecting the peripheral nervous system and skin. Multibacillary leprosy is associated with nerve damage which could contribute to myelin alteration. As ceramide is a constituent of myelin sheath, the present study aimed to compare anti-ceramide antibody titre in paucibacillary and multibacillary leprosy patients with controls. Methodology: Serum levels of anti-ceramide antibody were measured using enzyme-linked immunosorbent assays (ELISA) in 50 leprosy patients (25 paucibacillary and 25 multibacillary) and 25 healthy controls. Results were reported in OD units as mean ± SD and analyzed by Chi square test (significance at p < 0.05). Results: Patients suffering from multibacillary leprosy had significantly higher anti-ceramide antibody serum levels compared to paucibacillary leprosy patients and healthy controls (p < 0.005). Conclusions: Since nerve damage is the most debilitating effect of leprosy, the search for a serum marker for assessing nerve damage is required in countries where leprosy is still widespread. In multibacillary leprosy patients, the role of anti-ceramide antibody as a marker for nerve damage should be explored.